Detection of drugs in Australian prisons: supply reduction strategies. Issue 2 (10th June 2014) - Dolan, Kate; Rodas, Ana
Abstract : Purpose: – Prisoners have a high level of drug use prior to imprisonment. Many inmates report having injected drugs and using cannabis. Prison authorities employed a range of strategies to detect drugs and drug use in prison. However, it was unclear which supply reduction strategies operated, and the prevalence and types of drugs detected in Australian prisons. The purpose of this paper is to examine supply reduction strategies in Australian prisons. Information on searches for drugs, and from inmate urinalysis was collected. The study focussed on adults in fulltime custody in Australia in 2009. Design/methodology/approach: – A representative of all corrective services departments and justice health services was asked to complete a questionnaire on supply reduction strategies, including searches for drugs and drug testing of inmates. Findings: – The two main supply reduction strategies identified in all Australian prisons were the use of drug detection dogs and urinalysis programs. Despite an extensive use of drug searches and urinalysis, the detection of drugs was modest for both strategies. The most commonly used drug was cannabis with the detection of drugs such as amphetamines and heroin being very low. Research limitations/implications: – Prison inmates have a history of high levels of drug use prior to imprisonment. However, the supply reduction measures of drug detection dogs and urinalysis indicate that drug use was low in Australian prisons. Practical implications: – The paper recommends that urinalysis comprises targeting testing regimes and that random testing ceases in order to be a more cost effective use of resources for drug detection. Originality/value: – The study is the first report on the range of supply reduction measures in Australian prisons and, possibly in the world. Both measures were employed extensively across the country and finds of drugs and drug use were relatively low. Two possible conclusions can be drawn; that either drug use was very low in prison or that it was well concealed from the authorities. A comparison of random testing with targeted testing of inmates, where the former yields fewer positive results shows drug use was likely to be low rather than well concealed.